WORK BRICKWORK CRACKS IN THE TRANSFORMED INTERNAL VALVES ELEMENT - , А. Л., А. Е., А. А. (Municipal economy of cities (Technical science), 2013)
It was identified stress state of masonry reinforced with basalt-plastic in the crack zone.